Development of an advanced x-ray generator based on Compton back-scattering: a proposal for Science for Peace sub-program of NATO - Agafonov, A.V.; Botman, J.I.M.; Gladkikh, P.I.; Kachinskiy, A.V.; Karnaukhov, I.M.; Lebedev, A.N.; Mytsykov, A.O.; Shcherbakov, A.A.; Tatchyn, R.; Telegin, Yu.N.; van der Wiel, M.; Zelinsky, A.Yu. (Вопросы атомной науки и техники, 2001)
An extended form of a cooperative project proposal is presented. The main goal of the proposal is the design and construction of a storage ring X-ray generator based on Compton backscattering. The project’s primary objectives and organisation, together with a draft plan for the required N-100 storage ring reconstruction effort, are outlined.